2020
DOI: 10.1051/0004-6361/202038027
|View full text |Cite
|
Sign up to set email alerts
|

Annular substructures in the transition disks around LkCa 15 and J1610

Abstract: We present high-resolution millimeter continuum ALMA observations of the disks around the T Tauri stars LkCa 15 and 2MASS J16100501-2132318 (hereafter, J1610). These transition disks host dust-depleted inner regions, which have possibly been carved by massive planets, and they are of prime interest to the study of the imprints of planet-disk interactions. While at moderate angular resolution, they appear as a broad ring surrounding a cavity, the continuum emission resolves into multiple rings at a resolution o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 114 publications
(163 reference statements)
7
63
0
1
Order By: Relevance
“…• ) and that is obtained from continuum ALMA observations (50.16 • ± 0.03 • ; Facchini et al 2020) and suggests that the outer disk is misaligned with respect to the star+inner disk system. Similarly, in DoAr 44, Bouvier et al (2020) find that the stellar inclination is i = 30 • ± 5 • in agreement with our estimate of the inner disk inclination.…”
Section: Discussionmentioning
confidence: 60%
“…• ) and that is obtained from continuum ALMA observations (50.16 • ± 0.03 • ; Facchini et al 2020) and suggests that the outer disk is misaligned with respect to the star+inner disk system. Similarly, in DoAr 44, Bouvier et al (2020) find that the stellar inclination is i = 30 • ± 5 • in agreement with our estimate of the inner disk inclination.…”
Section: Discussionmentioning
confidence: 60%
“…Recent observations with ALMA of several transition disks showed that what was known to be a wide ring around a cavity is actually a composition of several narrow rings (e.g., Pérez et al 2020;Facchini et al 2020). A couple of ideas have been proposed to explain these narrow rings.…”
Section: Multiple Rings or Tail?mentioning
confidence: 99%
“…Pérez et al (2020) suggested that a single migrating low-mass planet (10 M ⊕ ) in between these rings can explain the multiple rings and their separation, but this planet cannot explain the formation of the cavity itself. Facchini et al (2020) demonstrated that the appearance of one ring or multiple rings depends on the assumptions of the thermodynamics in hydrodynamical simulations where a planet is assumed to be embedded inside the cavity. Alternatively, low values of the disk viscosity, both in hydrodynamical simulations and dust evolution models, can change the appearance of the disk that is hosting a giant planet, spanning appearances that suggest a compact disk all the way to those suggesting multiple rings and gaps (e.g., de Juan Ovelar et al 2016;Bae et al 2018).…”
Section: Multiple Rings or Tail?mentioning
confidence: 99%
“…The origin of these rings are still being debated, although disk-planet interaction is frequently invoked (Dipierro et al 2015;Liu et al 2018;Muley et al 2019;Toci et al 2020;Pinte et al 2020). Here, a common approach is to first perform 2D disk-planet simulations, then construct a 3D dust distribution assuming a turbulent diffusion model (e.g., Equation 27; Dubrulle et al 1995), before producing a synthetic image via radiative transfer and comparing it with observations (e.g., Dong et al 2015;Jin et al 2016;Facchini et al 2020).…”
Section: Inspirations To Observationsmentioning
confidence: 99%